Solid Electrolyte Interphase Growth in Lithium Metal Cells With Normal Electrolyte Flow - Parekh, Mihir N.; Rahn, Christopher D. (Frontiers in Chemical Engineering, 2022)
In high energy density lithium metal batteries (LMBs), dendrite and solid electrolyte interphase (SEI) growth reduce safety and longevity, respectively. A stable SEI layer enables high efficiency cycling but continued SEI growth can lead to reduced capacity and coulombic efficiency. In this paper, we develop a steady-state model that predicts the effect of small advective electrolyte flow towards the lithium metal electrode on SEI growth during charging. For a fixed current density, increasing the electrolyte flow rate improves the coulombic efficiency and decreases SEI layer growth rate. Decreasing the charging current density at a constant flow rate also decreases the SEI layer growth rate. Low flow rates μm/s can increase coulombic efficiency by up to 6 %. The sensitivity of the coulombic efficiency to plating and SEI layer reaction rates is also explored.